Meta Analysis of the Influence of Training on Work Productivity - Helvy Yunida; Riyadi; Iva Sarifah (East Asian Journal of Multidisciplinary Research, 2023)
Increasing employee competency will affect employee performance so that the employee's work becomes more effective and efficient. So that it is efficient and effective. The purpose of this research is to do a meta-analysis of the effect of training on work productivity. This research method uses meta-analysis, a type of multiple regression research, in which the researcher conducts a meta-analysis of 10 published journals with similar research. The results of this meta-analysis study show that there is a significant effect between training on employee work productivity. Based on the results of the Meta test Analysis of the correlation coefficient, the relationship between variables is strong because it is close to number 1. Based on the meta test Correlation coefficient analysis and effect size test on multiple regression tests, Count T tests, Count F tests, R Square tests and correlation tests. The data is positively heterogeneous and there is a significant influence or relationship between variables.